Scaling conservation agriculture-based sustainable intensification systems in Ethiopia - CGIAR Research Program on Maize (2018)
The Ethiopian Ministry of Agriculture has adopted conservation agriculture based sustainable extension package and cascade it to regional agriculture bureaus for implementation starting the small rainy season of 2019. A manual that guides the implementation of CA-based sustainable intensification is developed and distributed in local language.